Solar Energetic Particle Events with Extremely High 3He Content Observed by Solar Orbiter - A. Kouloumvakos; G. M. Mason; G. C. Ho; R. C. Allen; J. Rodriguez-Pacheco; R. F. Wimmer-Schweingruber (The Astrophysical Journal)
We performed a survey of ^3 He-rich events using observations from the Suprathermal Ion Spectrograph on the Solar Orbiter mission from 2020 to 2024. We identified 57 ^3 He-rich events, each showing clear ^3 He enhancements above the background and ^3 He/ ^4 He abundance ratios greater than 1 in at least one energy channel in the range from 193.2 keV nucleon ^−1 to 8.74 MeV nucleon ^−1 . The analysis of the events’ abundance ratios shows characteristics of impulsive solar energetic particle events with ^3 He/ ^4 He ∼ 3.1 and Fe/O ∼ 1.3. We observe an energy dependence in the ^3 He/ ^4 He ratio, which increases with energy, while the Fe/O ratios are almost constant with energy. We also found that six events in our list have extremely high ^3 He content (e.g., ^3 He/C–Fe ratios in the range 25–62). These events show curved ^3 He and heavy nuclei spectra that roll over at higher energies and flatten toward low energy. Their spectral forms can be reasonably fit with simple exponentials with a ^3 He rollover energy in the range of a few hundred keV per nucleon and a C–Fe rollover energy ∼2–3 times lower. The differences in spectral rollover energy lead to a strong energy dependence of the ratio ^3 He/C–Fe, rising sharply with energy. We conclude that the features of these events with extremely high ^3 He content have a reasonable likelihood of depicting the initial acceleration process, which is driven by magnetic reconnection in flaring loops near the solar surface.